Prototype Sistem Informasi Manajemen Potensi Desa Palasari Kecamatan Ujungjaya Kabupaten Sumedang Berbasis Website - Dony Waluya Firdaus (Labkat Press KA FTIK UNIKOM, 2018)
The information management is a bridge for the Government of the village in order to bring transparency and the use of the budget that has already absorbed. The prototype system management information the potential of rural palasari the district ujungjaya sumedang district based on the website using the primary and secondary stages in prototype is on the need, the process of design, building prototypes, evaluation and improvement.